Development of a Small-Capacity Tensile Testing Machine for Educational Demonstration - Paryana Puspaputra; Hendra Setiawan; Arif Rahman Hakim (Universitas Muhammadiyah Purwokerto, 2025)
The tensile testing machine is a device used to characterize the mechanical properties of materials. Most tensile testing machines currently available are designed for high-capacity applications, such as testing metals and concrete, making them less suitable for testing composite and plastic materials. Therefore, a small-capacity tensile testing machine that is more flexible and efficient is needed for testing and educational purposes. This study aims to develop and improve the performance of a small-capacity tensile testing machine by enhancing its control system and human interface. Improvements include increasing the displacement sensor sensitivity from 200 mm to 50 mm, using a load cell with a more appropriate capacity (reduced from 2 tons to 1 ton), and adding a data logging feature via USB in text format. The test results indicate that the developed system is capable of performing tensile tests in accordance with ASTM D638 standards, with higher accuracy compared to the previous version. The implementation of the new control system also enables better data recording, thereby enhancing the machine's reliability as a tool for education and research.